Circadian rhythms driving a fast‐paced root clock implicate species‐specific regulation in Medicago truncatula. Issue 8 (7th July 2021) - Wang, Liping; Zhou, Anqi; Li, Jing; Yang, Mingkang; Bu, Fan; Ge, Liangfa; Chen, Liang; Huang, Wei
Abstract: Plants have a hierarchical circadian structure comprising multiple tissue‐specific oscillators that operate at different speeds and regulate the expression of distinct sets of genes in different organs. However, the identity of the genes differentially regulated by the circadian clock in different organs, such as roots, and how their oscillations create functional specialization remain unclear. Here, we profiled the diurnal and circadian landscapes of the shoots and roots of Medicago truncatula and identified the conserved regulatory sequences contributing to transcriptome oscillations in each organ. We found that the light‐dark cycles strongly affect the global transcriptome oscillation in roots, and many clock genes oscillate only in shoots. Moreover, many key genes involved in nitrogen fixation are regulated by circadian rhythms. Surprisingly, the root clock runs faster than the shoot clock, which is contrary to the hierarchical circadian structure showing a slow‐paced root clock in both detached and intact Arabidopsis thaliana (L.) Heynh. roots. Our result provides important clues about the species‐specific circadian regulatory mechanism, which is often overlooked, and possibly coordinates the timing between shoots and roots independent of the current prevailing model. Abstract : Profiles of the diurnal and circadian landscapes of the transcriptome oscillations in shoots and roots of Medicago truncatula revealed that the root clock of M. truncatula runs faster than the shoot clock, which is contrary to the hierarchical coupling model of Arabidopsis thaliana, suggesting speciesspecific regulation in M. truncatula .